Towards Winter Seasonal Predictability of the North West European Shelf Seas - Tinker, Jonathan; Hermanson, Leon (Frontiers in Marine Science, 2021)
We investigate the winter predictability of the North West European shelf seas (NWS), using the Met Office seasonal forecasting system GloSea5 and the Copernicus NWS reanalysis. We assess GloSea5’s representation of NWS climatological winter and its skill at forecasting winter conditions on the NWS. We quantify NWS winter persistence and compare this to the forecast skill. GloSea5 simulates the winter climatology adequately. We find important errors in the residual circulation (particularly in the Irish Sea) that introduce temperature and salinity biases in the Irish Sea, English Channel, and southern North Sea. The GloSea5 winter skill is significant for SST across most of the NWS but is lower in the southern North Sea. Salinity skill is not significant in the regions affected by the circulation errors. There is considerable NWS winter temperature and salinity persistence. GloSea5 exhibits significant predictive skill above this over 20% of the NWS, but for most of the NWS this is not the case. Dynamical downscaling is one method to improve the GloSea5 simulation of the NWS and its circulation, which may reduce biases and increase predictive skill. We investigate this approach with a pair of case studies, comparing the winters of 2010/2011 and 2011/2012 (with contrasting temperature and salinity anomalies, and NAO state). While two years are insufficient to assess skill, the differences in the simulations are evaluated, and their implications for the NWS winter predictability are considered. The NWS circulation is improved (where it was poor in the GloSea5), allowing more realistic advective pathways for salinity (and temperature) and enhancing their climatological spatial distributions. However, as the GloSea5 SST anomaly is already well simulated, downscaling does not substantially improve this – in other seasons or for other variables, downscaling may add more value. We show that persistence of early winter values provides some predictive skill for the NWS winter SST, and that the GloSea5 system adds modestly to this skill in certain regions. Such information will allow prospective end-users to consider how seasonal forecasts might be useful for their sector, providing the foundation on which marine environmental seasonal forecasts service and community may be developed.